THE EFFECT OF PEMPEK BREAKFAST ON SHORT TERM MEMORY IN STUDENTS AT PSYCHOLOHY STUDY PROGRAM UIN RADEN FATAH PALEMBANG - Zahirah, Siti Alicia; Puspita, Adelia; Fauzian , Cheazar Haqqy; Nabela , Nency; Simatupang, Sheva Semara; Az-Zahaby, M Fawwaz; Al-Qolba Sugun, Maula Habib; Rahayu, Riski Tiara; Sintia, Tezzy Maria; Putri, Nur Amalia (CV. Era Digital Nusantara, 2022)
A lot of theory and research said that breakfast can improve someone’s short term memory. The purpose of this research is to find out wether breakfast really improve short term memory or not. This research used quasi-experimental with control group design. There’s 30 students of Psychology students at Raden Fatah State Islamic University Palembang, 15 as subjects who were given breakfast, 15 as control group subjects who were not given breakfast. Subjects have an age range between 19-20 years old, all of subject are those who are accustomed to breakfast. Subject given pempek as the breakfast. Memory test used is biopsycologytes, performed twice, before breakfast and 3 minute after material. The result of this study are there is a significant difference in short term memory scores between subjects given breakfast and subjects not given breakfast with p = 0,00 withpaired sample t-test technique. Conclusion of this research is, breakfast has an effect to short term memory.